Portfolio investment flows and the Lucas paradox – an evidence from the global economy in the 21 st century - Broszkiewicz, Magdalena (Economics of the 21st Century, 2017)
The aim of this article is to examine the flow of portfolio investment in the 21st century in the further use of the Lucas paradox observed in the world economy in the twentieth century. Portfolio investments are perceived in the literature and empirical research as less significant, while both their size and importance to the development of capital markets are usually only indicated. Data for the study were obtained from the balance of payments of individual countries and groups of countries, as well as data on the size and level of development of capital markets in these groups. The course of this research confirmed the importance of the flow of capital in the form of portfolio investments in the global economy. This has shown the further occurrence of the Lucas paradox, also in portfolio investment. It shows the weakness of the capital markets of LDCs in conjunction with the insufficient inflow of portfolio investments. The originality of the article lies in the combination of portfolio investments and determinants of the attractiveness of individual capital markets for investors in international financial markets. The small inflow of portfolio investments is both the cause and the consequence of the insufficient level of development of capital markets in the least developed countries (LDC). Hence the need to make a diagnosis and to build paths of development of such markets based on the experience of more developed countries, in order to adapt them to attract and retain capital in the form of portfolio investments
Ekonomia XXI Wieku = Economics of the 21st Century, 2017, Nr 3 (15), s. 91-105
Keywords: portfolio investment; international capital flows; capital markets; Lucas paradox; inwestycje portfelowe; międzynarodowe przepływy kapitału; rynki kapitałowe; paradoks Lucasa